Method for manufacturing liner tube and liner tube

By adopting OVD deposition, fluorine-doping and OVD sintering steps in optical fiber manufacturing, the shortcomings of existing liners in doping depth and uniformity are solved, and a liner with high doping depth and good uniformity is achieved Production improves the optical signal conduction capability of optical fibers.

CN119390341APending Publication Date: 2025-02-07WUHAN FEILING OPTOELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321550.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The liner used in the existing optical fiber manufacturing has shortcomings in doping depth and uniformity, which is difficult to meet the demand for high doping depth, and the uniformity of the glass axial direction is not good.

Method used

Through OVD deposition, fluorine doping and OVD sintering steps, the doping flow rate, doping temperature and doping time are controlled to prepare liners with high doping depth and good uniformity.

Benefits of technology

The production of liner tubes with doped thickness of 0-8mm and NA range of 0-0.35 is achieved, and the light incident angle and optical signal conduction ability of the optical fiber are improved, which is suitable for low-light loss applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390341A_ABST
    Figure CN119390341A_ABST
Patent Text Reader

Abstract

The invention discloses a method for manufacturing a liner tube and the liner tube. The method comprises the steps of OVD deposition, fluorine introduction doping and OVD sintering. In the step of OVD deposition, extension rods are connected to the two ends of the glass rod, then the glass rod is installed on OVD deposition equipment, the OVD equipment is started for deposition on the glass rod, and loose silicon dioxide is obtained; the fluorine introduction doping comprises the following steps: after the OVD deposition is completed, moving a glass rod into an OVD sintering furnace, increasing the temperature in the sintering furnace, introducing chlorine gas to dehydrate a loose body, introducing carbon tetrafluoride or sulfur hexafluoride gas into the sintering furnace, and doping fluorine; after fluorine doping is completed, OVD sintering is carried out, and after OVD sintering is completed, the loose silicon dioxide particles are converted into glass in a transparent state. The method is simple, convenient and easy to control, the geometric dimension and the relative refractive index coefficient of the produced liner tube are more convenient to control, and the production cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical fiber manufacturing, and in particular relates to a method for manufacturing a liner tube and a liner tube used in the optical fiber manufacturing industry. Background Art

[0002] In the optical fiber manufacturing industry, liners are widely used. The liner is a sleeve structure with a cylindrical exterior and a hollow interior. The solid part of the liner is not pure quartz glass, but is usually doped with other substances to make its relative refractive index lower than that of pure quartz glass. Liners are widely used in the optical fiber manufacturing industry. In the preparation processes such as PCVD and MCVD, the liner is used as a deposition carrier and is installed at both ends of the PCVD or MCVD equipment. Silicon tetrachloride or germanium tetrachloride and the reaction gas pass through the liner and react in the inner cavity of the liner. The silicon dioxide or germanium dioxide particles produced by the reaction are adsorbed on the inner wall of the liner. In the optical fiber manufacturing process, the liner not only provides an environmental carrier for the reaction of silicon tetrachloride or germanium tetrachloride, but also provides a collection of silicon dioxide or germanium dioxide and other substances produced by the above reaction. At the same time, due to the special refractive index structure of the liner, it is an important part of the optical fiber waveguide structure.

[0003] The liner is also used in the shrinking process in optical fiber manufacturing. The liner and core rod are assembled together and shrunk into one by a shrinking lathe.

[0004] Conventional liner manufacturing methods usually use blowing, drawing or pressing to make liquid glass into hollow liner. However, such liner generally does not have doping ability. Even if some doping processes are added, the doping thickness is 0.2-2mm, NA is less than or equal to 0.12, and the uniformity is poor. The manufacturing method used in the present invention can meet a very high doping depth while ensuring the uniformity of the glass axial direction. Summary of the invention

[0005] Based on the above description, the present invention provides a method for manufacturing a liner and a liner. The method is simple and convenient. By controlling the dopant flow rate, doping temperature, and doping time, the geometric dimensions and relative refractive index coefficient of the produced liner are easier to control and the production cost is low.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A method for manufacturing a liner tube, comprising the steps of OVD deposition, fluorine doping, and OVD sintering;

[0008] The OVD deposition: After connecting extension rods at both ends of the glass rod, install it on the OVD deposition equipment, turn on the OVD equipment to perform deposition on the glass rod to obtain loose silicon dioxide;

[0009] The fluorine doping: after the OVD deposition is completed, the glass rod is moved into the OVD sintering furnace, the temperature in the sintering furnace is increased, chlorine gas is first introduced to dehydrate the loose body, and then carbon tetrafluoride or sulfur hexafluoride gas is introduced into the sintering furnace to dope fluorine;

[0010] After fluorine doping is completed, OVD sintering is performed. After OVD sintering is completed, the loose silica particles are transformed into transparent glass.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Furthermore, the method also includes a punching step: taking out the sintered glass rod, cutting both ends into a flat state, moving it to a punching device, and punching a hole centered at the center point of the flat surface to obtain a punched rod.

[0013] Furthermore, it also includes a stretching step: after the punching is completed, one end is connected to an extension tube; the punching rod with the extension tube is moved to a stretching tower for stretching.

[0014] Furthermore, during the stretching process, protective gas is always injected into the punch rod from the end face of the extension tube, so that the internal air pressure of the punch rod is kept consistent with the external air pressure.

[0015] Furthermore, the glass rod is a conventional glass rod or a high-purity quartz glass rod.

[0016] Furthermore, in the fluorine doping step, the temperature in the sintering furnace is increased to 1000-1200°C.

[0017] Furthermore, the temperature of the OVD sintering step is 1400-1600°C.

[0018] Furthermore, in the fluorine doping step, the temperature in the sintering furnace is increased to 1100°C.

[0019] Furthermore, the temperature of the OVD sintering step is 1500°C.

[0020] Furthermore, in the fluorine doping, the concentration of the chlorine gas is 3 SLM, and the introduction time is 1.5-3.5 hours.

[0021] Furthermore, in the fluorine doping, when the fluorine doping gas is carbon tetrafluoride, the flow rate of the carbon tetrafluoride is: 4SLM, and the doping time is 0.5-6 hours.

[0022] Furthermore, when the fluorine-doped gas is sulfur hexafluoride, the flow rate of the sulfur hexafluoride is 3 SLM, and the doping time is 0.5-6 hours.

[0023] Furthermore, the OVD sintering time after fluorine doping is 2 hours.

[0024] A liner pipe is made by any of the methods described above.

[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0026] Through the above steps, the present invention can obtain a liner with a doping thickness of 0-8 mm and a NA of 0-0.35. The larger the NA, the greater the light incident angle that the optical fiber can accept, and thus can transmit more optical signals. The optical fiber with high NA is suitable for applications with low optical loss, especially in transmission over shorter distances.

[0027] The present invention can control the doping thickness by conditions such as doping concentration, doping temperature, and doping time, and the doping thickness ranges from 0 to 8 mm;

[0028] The present invention can achieve uniform doping consistency through process conditions such as doping temperature and rotation;

[0029] The present invention can control the doping depth of the liner to 1 to 8 mm through process conditions such as drilling and stretching;

[0030] The present invention can control the out-of-roundness index of the liner to ≤0.5 (%) through process conditions such as punching and stretching;

[0031] The present invention can control the curvature (mm / m) index of the liner to ≤0.5 through drilling, stretching and other process conditions; the present invention can control the outer diameter tolerance index of the liner to reach ±0.4mm through drilling, stretching and other process conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A process flow chart of a method for manufacturing a liner provided by an embodiment of the present invention;

[0033] Figure 2 A refractive index diagram of a liner tube obtained by the method provided in Example 1 of the present invention;

[0034] Figure 3 A refractive index diagram of a liner tube obtained by the method provided in Example 2 of the present invention;

[0035] Figure 4 A refractive index diagram of a liner tube obtained by the method provided in Example 3 of the present invention;

[0036] Figure 5 A refractive index diagram of a liner tube obtained by the method provided in Example 4 of the present invention;

[0037] Figure 6 The refractive index diagram of the liner tube prepared by the method provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0039] First, connect the extension rods on both sides of a glass rod and install it on the OVD deposition equipment. This glass can be an ordinary glass rod or a high-purity quartz glass rod; turn on the OVD equipment to deposit on the glass rod. At this time, the raw material silicon tetrachloride and the reaction gas directly undergo hydrolysis reaction, and the silicon dioxide produced by the reaction is deposited on the glass rod in the form of loose body; after the OVD deposition is completed, move the glass rod to the OVD sintering furnace; at this time, the temperature in the sintering furnace is raised to about 1100℃, chlorine gas is first introduced to dehydrate the loose body, and then carbon tetrafluoride or sulfur hexafluoride gas is introduced into the sintering furnace to carry out the fluorine doping process; the temperature of the sintering furnace is raised to about 1500℃ for sintering. After sintering, the loose body silicon dioxide particles are transformed into transparent glass.

[0040] The sintered glass rod is taken out, both ends are cut into a flat state, and moved to the punching equipment, and holes are punched with the center point of the flat surface (i.e., the two end faces of the rod) as the center; after the drilling is completed, one end is connected to an extension tube; the punching rod with the extension tube is moved to the stretching tower for stretching, and during the stretching process, protective gas is always injected into the punching rod from the end face of the extension tube to keep the internal air pressure of the punching rod consistent with the external air pressure; stretching is performed according to the target liner size, and finally a liner with the required geometric size and a liner with a special zone relative refractive index coefficient can be obtained.

[0041] The concentration of the chlorine gas is: 3SLM, and the introduction time is: (1.5-3.5) hours.

[0042] When the fluorine-doped gas is carbon tetrafluoride, the concentration of the carbon tetrafluoride is 4 SLM, and the doping time is (0.5-6) ​​hours.

[0043] When the fluorine-doped gas is sulfur hexafluoride, the concentration of the sulfur hexafluoride is 3 SLM, and the doping time is (0.5-6) ​​hours.

[0044] The time of OVD sintering after fluorine doping is (1-6) hours.

[0045] The present invention can obtain a doped liner tube with NA in the range of 0 to 0.35 through the above steps;

[0046] The present invention can control the doping thickness by conditions such as doping concentration, doping temperature, and doping time, and the doping thickness ranges from 0 to 8 mm;

[0047] The present invention can achieve uniform doping consistency through process conditions such as doping temperature and rotation;

[0048] The present invention can control the doping depth of the liner to 1 to 8 mm through process conditions such as drilling and stretching;

[0049] The present invention can control the out-of-roundness index of the liner to ≤0.5 (%) through process conditions such as punching and stretching;

[0050] The present invention can control the curvature (mm / m) index of the liner to ≤0.5 through the process conditions such as punching and stretching;

[0051] The present invention can control the outer diameter tolerance index of the liner to reach ±0.4 through process conditions such as drilling and stretching.

[0052] Example 1

[0053] The present invention is further described below in conjunction with embodiments and drawings.

[0054] A 40mm outer diameter glass rod with extension rods at both ends is installed on the OVD equipment, the OVD equipment door is closed, and the deposition is started. When the outer diameter of SOOT (powder) is 140mm, the OVD deposition system is turned off; after the SOOT body is cooled, it is moved to the sintering equipment; the furnace temperature of the sintering equipment is raised to 1100°C, and 3SLM of chlorine gas is introduced for 2h to dehydrate the SOOT body; after dehydration is completed, sulfur hexafluoride gas with a concentration of 99.99% is introduced into the sintering furnace, and the sulfur hexafluoride flow rate is 3SLM, and deep fluorine doping is carried out at 1110°C for two hours; after fluorine doping is completed, the sintering furnace temperature is raised to 1530°C for sintering, and a preform rod with an outer diameter of 80 mm is obtained after sintering.

[0055] After sintering, the preform rod with an outer diameter of 80mm is taken out, and both ends are cut into a flat state, and moved to the punching equipment. A 71mm diameter drill is used to punch holes centered on the center point of the flat surface. At this time, a casing with an outer diameter of 80mm and an inner diameter of 71mm is obtained; the two ends of this casing are connected to extension tubes and stretched in a stretching tower. During the stretching process, protective gas is always injected into the punching rod from the end face of the extension tube to keep the internal air pressure of the punching rod consistent with the external air pressure; the rod feeding rate and the stretching rate of the stretching tower are controlled to obtain a liner with an outer diameter of 36mm and an inner diameter of 32mm.

[0056] The refractive index test of the liner with an outer diameter of 36 mm and an inner diameter of 32 mm is carried out. Figure 2As shown in the figure, along the length direction of the liner, 5 points of 50mm, 150mm, 250mm, 350mm and 450mm were selected for refractive index testing. It can be seen from the figure that along the length direction of the liner, the refractive index is evenly distributed. The test results show that the refractive index distribution is as follows Figure 2 , doping thickness is 2mm, NA=0.20.

[0057] The bow degree of the liner was measured, and the bow degree (mm / m) index was ≤0.25.

[0058] According to the principle that the out-of-roundness is equal to the diameter difference divided by the average diameter multiplied by 100%, the out-of-roundness corresponding to the preset measuring point is calculated. The out-of-roundness of the liner is measured, and the out-of-roundness index is ≤0.25 (%).

[0059] Example 2

[0060] A 40mm outer diameter glass rod with extension rods at both ends is installed on the OVD equipment, the OVD equipment door is closed, and the deposition is started by ignition. When the outer diameter of SOOT (powder) is 210mm, the OVD deposition system is turned off; after the SOOT body is cooled, it is moved to the sintering equipment; the furnace temperature of the sintering equipment is raised to 1120°C, and chlorine gas is introduced to dehydrate the SOOT body; after dehydration is completed, 4SLM of carbon tetrafluoride gas is introduced into the sintering furnace, and fluorine is doped at 1105°C for 1.5 hours; after fluorine doping is completed, the sintering furnace temperature is raised to 1540°C for sintering, and a preformed rod with an outer diameter of 115 mm is obtained after sintering.

[0061] After sintering, the preform rod with an outer diameter of 115mm is taken out, and both ends are cut into a flat state, and moved to the punching equipment. A drill bit with a diameter of 80mm is used to punch holes centered on the center point of the flat surface. At this time, a casing with an outer diameter of 115mm and an inner diameter of 80mm is obtained; the two ends of this casing are connected to extension tubes and stretched in a stretching tower. During the stretching process, protective gas is always injected into the punching rod from the end face of the extension tube to keep the internal air pressure of the punching rod consistent with the external air pressure; the rod feeding rate and the stretching rate of the stretching tower are controlled to obtain a liner with an outer diameter of 26mm and an inner diameter of 18mm.

[0062] The refractive index test of the liner with an outer diameter of 26 mm and an inner diameter of 18 mm is carried out. Figure 3 As shown in the figure, along the length direction of the liner, 5 points of 50mm, 150mm, 250mm, 350mm and 450mm were selected for refractive index testing. It can be seen from the figure that along the length direction of the liner, the refractive index is evenly distributed. The test results show that the refractive index distribution is as follows Figure 3 , doping thickness is 4mm, NA=0.15.

[0063] The bow degree of the liner was measured, and the bow degree (mm / m) index was ≤0.4.

[0064] According to the principle that the out-of-roundness is equal to the diameter difference divided by the average diameter multiplied by 100%, the out-of-roundness corresponding to the preset measuring point is calculated. The out-of-roundness of the liner is measured, and the out-of-roundness index is ≤0.4 (%).

[0065] Example 3

[0066] Install a 40mm outer diameter glass rod with extension rods at both ends onto the OVD equipment, close the OVD equipment door, ignite and start deposition, and turn off the OVD deposition system when the SOOT (powder) outer diameter is 164mm; after the SOOT body is cooled, move it to the sintering equipment; raise the furnace temperature of the sintering equipment to 1130℃, and then introduce chlorine gas to dehydrate the SOOT body; after dehydration is completed, introduce 5SLM of sulfur hexafluoride gas into the sintering furnace, and perform deep fluorine doping at 1130℃ for 4 hours; after fluorine doping is completed, raise the sintering furnace temperature to 1550℃ for sintering, and obtain a preform rod with an outer diameter of 93mm after sintering.

[0067] After sintering, the preform rod with an outer diameter of 93mm is taken out, and both ends are cut into a flat state, and moved to the punching equipment. A drill bit with a diameter of 80mm is used to punch holes centered on the center point of the flat surface. At this time, a casing with an outer diameter of 130mm and an inner diameter of 80mm is obtained; the two ends of this casing are connected to extension tubes and stretched in a stretching tower. During the stretching process, protective gas is always injected into the punching rod from the end face of the extension tube to keep the internal air pressure of the punching rod consistent with the external air pressure; the rod feeding rate and the stretching rate of the stretching tower are controlled to obtain a liner with an outer diameter of 28mm and an inner diameter of 24mm.

[0068] The refractive index test of the liner with an outer diameter of 28 mm and an inner diameter of 24 mm is carried out. Figure 4 As shown in the figure, along the length direction of the liner, 5 points of 50mm, 150mm, 250mm, 350mm and 450mm were selected for refractive index testing. It can be seen from the figure that along the length direction of the liner, the refractive index is evenly distributed. The test results show that the refractive index distribution is as follows Figure 4 , doping thickness is 2mm, NA=0.3.

[0069] The bow degree of the liner was measured, and the bow degree (mm / m) index was ≤0.3.

[0070] According to the principle that the out-of-roundness is equal to the diameter difference divided by the average diameter multiplied by 100%, the out-of-roundness corresponding to the preset measuring point is calculated. The out-of-roundness of the liner is measured, and the out-of-roundness index is ≤0.3 (%).

[0071] Example 4

[0072] This embodiment is basically the same as Embodiment 1, except that:

[0073] The sulfur hexafluoride flow rate is 4SLM, and deep fluorine doping is carried out at 1110° C. for two hours. After the fluorine doping is completed, the sintering furnace temperature is increased to 1530° C. for sintering, and a preformed rod with an outer diameter of 80 mm is obtained after sintering.

[0074] The refractive index test of the liner with an outer diameter of 36 mm and an inner diameter of 32 mm is carried out. Figure 5 As shown in the figure, along the length direction of the liner, 5 points of 50mm, 150mm, 250mm, 350mm and 450mm were selected for refractive index testing. It can be seen from the figure that along the length direction of the liner, the refractive index is evenly distributed. The test results show that the refractive index distribution is as follows Figure 5 , doping thickness is 2mm, NA=0.23.

[0075] The bow degree of the liner was measured, and the bow degree (mm / m) index was ≤ 0.27.

[0076] According to the principle that the out-of-roundness is equal to the diameter difference divided by the average diameter multiplied by 100%, the out-of-roundness corresponding to the preset measuring point is calculated. The out-of-roundness of the liner is measured, and the out-of-roundness index is ≤0.27 (%).

[0077] Example 5

[0078] This embodiment is basically the same as Embodiment 2, except that:

[0079] The carbon tetrafluoride flow rate is 4SLM, and deep fluorine doping is carried out at 1110° C. for 3 hours; after the fluorine doping is completed, the sintering furnace temperature is increased to 1530° C. for sintering, and a preformed rod with an outer diameter of 115 mm is obtained after sintering.

[0080] The refractive index test of the liner with an outer diameter of 26 mm and an inner diameter of 18 mm is carried out. Figure 6 As shown in the figure, along the length direction of the liner, 5 points of 50mm, 150mm, 250mm, 350mm and 450mm were selected for refractive index testing. It can be seen from the figure that along the length direction of the liner, the refractive index is evenly distributed. The test results show that the refractive index distribution is as follows Figure 6 , doping thickness is 4mm, NA=0.20.

[0081] The bow degree of the liner was measured, and the bow degree (mm / m) index was ≤0.43.

[0082] According to the principle that the out-of-roundness is equal to the diameter difference divided by the average diameter multiplied by 100%, the out-of-roundness corresponding to the preset measuring point is calculated. The out-of-roundness of the liner is measured, and the out-of-roundness index is ≤0.43 (%).

[0083] According to Example 1, Example 3, and Example 4, when the sulfur hexafluoride flow rate increases, the NA of the fluorine-doped liner obtained will increase, and at the same time, its curvature will increase, and the out-of-roundness will increase; Compared with Example 2, Example 5 mainly increases the sintering time from 1.5h to 3h. It can be seen that by extending the sintering time, the NA of the fluorine-doped liner obtained will increase, and at the same time, its curvature will increase, and the out-of-roundness will increase. The carbon tetrafluoride flow rate will also affect the performance of the liner. When the carbon tetrafluoride flow rate is low, the NA of the fluorine-doped tube obtained will become smaller, and at the same time, its curvature will become smaller, and the out-of-roundness will become smaller. In addition, the sintering temperature will also affect the performance of the liner. When the sintering temperature is lowered, the doping thickness of the preform obtained will be smaller, the NA will become smaller, and at the same time, its curvature will become smaller, and the out-of-roundness will become smaller.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for manufacturing a liner, characterized in that: It includes OVD deposition, fluorine doping, and OVD sintering steps; The OVD deposition: After connecting extension rods at both ends of the glass rod, install it on the OVD deposition equipment, turn on the OVD equipment to perform deposition on the glass rod to obtain loose silicon dioxide; The fluorine doping: after the OVD deposition is completed, the glass rod is moved into the OVD sintering furnace, the temperature in the sintering furnace is increased, chlorine gas is first introduced to dehydrate the loose body, and then carbon tetrafluoride or sulfur hexafluoride gas is introduced into the sintering furnace to dope fluorine; After fluorine doping is completed, OVD sintering is performed. After OVD sintering is completed, the loose silica particles are transformed into transparent glass.

2. A method for manufacturing a liner according to claim 1, characterized in that: The method also includes a punching step: taking out the sintered glass rod, cutting both ends into a flat state, moving the rod to a punching device, and punching a hole with the center point of the flat surface as the center to obtain a punched rod.

3. A method for manufacturing a liner according to claim 2, characterized in that: The method also includes a stretching step: after the punching is completed, one end is connected to an extension tube; and the punching rod with the extension tube is moved to a stretching tower for stretching.

4. A method for manufacturing a liner according to claim 3, characterized in that: During the stretching process, protective gas is always injected into the punch rod from the end face of the extension tube, so that the internal air pressure of the punch rod is consistent with the external air pressure.

5. A method for manufacturing a liner according to claim 1, characterized in that: The glass rod is a conventional glass rod or a high-purity quartz glass rod.

6. A method for manufacturing a liner according to claim 1, characterized in that: In the fluorine doping step, the temperature in the sintering furnace is increased to 1000-1200°C.

7. A method for manufacturing a liner according to claim 1, characterized in that: The temperature of the OVD sintering step is 1400-1650°C.

8. A method for manufacturing a liner according to claim 6, characterized in that: In the fluorine doping step, the temperature in the sintering furnace is increased to 1100°C.

9. A method for manufacturing a liner according to claim 7, characterized in that: The temperature of the OVD sintering step is 1500°C.

10. A liner pipe, characterized in that: The method is prepared by any one of claims 1 to 9.